The Effect of Functional Strength Training On The Development Of Special Requirement On Rings For Youth Gymnasts - Majeed, Saleh (Journal of Physical Education, 2016)
The aim of the research is to design functional strength exercises for developing special requirements that affect the working muscles of ring performance in gymnastics. The researcher used the experimental method. The subjects were (6) youth gymnasts. Three pilot tests were conducted followed by the main experiment to identify the operation method of EMG and displaying the results through Myo Research. The experiments were conducted 20/7/2016 till 25/11/2015. The researchers collected the data and treated it using proper statistical operations. The researchers concluded that the standardized training loads using the training program contributed in developing the performance of gymnasts. In addition to that they concluded that using EMG gave clear indicators for development or weaknesses in performance. Finally the researcher recommended equipping training gyms with functional strength training equipment due to their great effect on skill and physical development. They also recommended making periodical functional tests to evaluate the gymnast's development as well as using videotaping and motor analysis for correcting motor pathways of skills in younger athletes.